2019
DOI: 10.1007/s00270-019-02312-8
|View full text |Cite
|
Sign up to set email alerts
|

68Ga-PSMA-PET/CT and Diffusion MRI Targeting for Cone-Beam CT-Guided Bone Biopsies of Castration-Resistant Prostate Cancer Patients

Abstract: Introduction Precision medicine expands the treatment options for metastatic castration-resistant prostate cancer (mCRPC) by targeting druggable genetic aberrations. Aberrations can be identified following molecular analysis of metastatic tissue. Bone metastases, commonly present in mCRPC, hinder precision medicine due to a high proportion of biopsies with insufficient tumor cells for nextgeneration DNA sequencing. We aimed to investigate the feasibility of incorporating advanced target planning and needle gui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Recently, fused images of 68 Ga-PSMA PET/CT and diffusion weighted MRI, in combination with conebeam CT guidance, have been applied to guide bone biopsies in patients with prostate cancer. Though in a small number of patients (N=10), this pilot study showed a success rate of 80% (14). Therefore, 68 Ga-PSMA PET/CT is a promising technique to increase the success rate of bone biopsies for molecular analyses in prostate cancer patients.…”
Section: Introductionmentioning
confidence: 84%
“…Recently, fused images of 68 Ga-PSMA PET/CT and diffusion weighted MRI, in combination with conebeam CT guidance, have been applied to guide bone biopsies in patients with prostate cancer. Though in a small number of patients (N=10), this pilot study showed a success rate of 80% (14). Therefore, 68 Ga-PSMA PET/CT is a promising technique to increase the success rate of bone biopsies for molecular analyses in prostate cancer patients.…”
Section: Introductionmentioning
confidence: 84%
“…Another retrospective multicenter study indicated that both HU mean and SUV max variables from CT and 68 Ga-PSMA PET imaging, associate with an outcome of at least 30% tumor content in bone biopsies [ 21 ]. In a previous published prospective study of ten mCRPC patients, advanced planning with 68 Ga-PSMA PET and diffusion-weighted MRI increased diagnostic yield up to 90% on cone-beam CT-guided biopsy [ 26 ]. Further prospective studies are needed to assess and validate radiomic signatures to predict bone biopsy outcome utilizing CT, MRI and PSMA PET imaging modalities.…”
Section: Discussionmentioning
confidence: 99%
“…To compensate for the shortcomings of CT, some authors advocate using PET/CT to identify bone biopsy targets [ 15 , 16 ]. Recently published data on using prostate-specific membrane antigen (PSMA)-PET/CT for bone biopsy targeting in prostate cancer patients improved NGS feasibility rates up to 70–90% [ 12 , 17 , 18 ]. Remarkably, although being recognised as the gold standard imaging method for detecting malignant bone diseases, MRI features that are associated with a positive bone biopsy or NGS outcome have not been described [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%